Cobalt‐Catalyzed Enantioselective Hydroamination of Arylalkenes with Secondary Amines. (5th December 2022) - Miao, Huanran; Guan, Meihui; Xiong, Tao; Zhang, Ge; Zhang, Qian
Abstract: Catalytic asymmetric hydroamination of alkenes with Lewis basic amines is of great interest but remains a challenge in synthetic chemistry. Here, we developed a Co‐catalyzed asymmetric hydroamination of arylalkenes directly using commercially accessible secondary amines. This process enables the efficient access to valuable α ‐chiral tertiary amines in good to excellent yields and enantioselectivities. Mechanistic studies suggest that the reaction includes a CoH‐mediated hydrogen atom transfer (MHAT) with arylalkenes, followed by a pivotal catalyst controlled SN 2‐like pathway between in situ generated electrophilic cationic alkylcobalt(IV) species and free amines. This radical‐polar crossover strategy not only provides a straightforward and alternative approach for the synthesis of enantioenriched α ‐tertiary amines, but also underpins the substantial opportunities in developing asymmetric radical functionalization of alkenes with various free nucleophiles in oxidative MHAT catalysis. Abstract : An excellent enantioselective hydroamination of arylalkenes with Lewis basic secondary amines was developed, via an elegant cobalt‐hydride mediated oxidative hydrogen atom transfer (MHAT) process, leading to the synthesis of a series of valuable α ‐chiral tertiary amines in good to excellent yields and enantioselectivities.